Development and validation of a high‐sensitivity assay for measuring p217+tau in plasma. Issue 1 (27th May 2021) - Triana‐Baltzer, Gallen; Moughadam, Setareh; Slemmon, Randy; Van Kolen, Kristof; Theunis, Clara; Mercken, Marc; Kolb, Hartmuth C.
Abstract: Introduction: Diagnosis of Alzheimer's disease (AD) based on amyloid beta (A), pathologic tau (T), and neurodegeneration (N) biomarkers in peripheral fluids promises to accelerate clinical trials and intercept disease earlier. Methods: Qualification of a Simoa plasma p217+tau assay was performed, followed by clinical utility evaluation in a cohort of 227 subjects with broad A and T spectrum. Results: The p217+tau plasma assay was accurate, precise, dilution linear, and highly sensitive. All measured samples were within linear range of the assay, presented higher concentration in AD versus healthy controls ( P  < .0001), and plasma and cerebrospinal fluid levels correlated (r 2  = 0.35). The plasma p217+tau results were predictive of central T and A status (area under the curve = 0.90 and 0.90, respectively) with low false +/– rates. Discussion: The assay described here exhibits good technical performance and shows potential as a highly accurate peripheral biomarker for A or T status in AD and cognitively normal subjects.